Confucian or confusion? Analyses of international students’ self-rated intercultural sensitivity and its sociocultural predictors at Canadian universities - Yuan, Xuechen (Frontiers in Education, 2023)
In mainstream psychological research, Confucian heritage culture is often the scapegoat for subjecting Confucian heritage culture students to cultural archetypes of reticence, obedience, and unassailability, leading to the stigmatization of international students. This study examines differences in international students' self-rated intercultural sensitivity and the potential discrepancy that exists between large-scale differences in sociocultural dimensions and student perceptions of these dimensions. International students were divided into two groups: Confucian and non-Confucian groups. The quantitative analyses found that 1) Confucian heritage culture has little predictive value to intercultural sensitivity; 2) Confucian group does not uniquely identify with Confucian values; 3) Second language apprehension, as the sole predictor, accounts for more variation in intercultural sensitivity than most sociocultural predictors combined. This study demonstrates that deterministic views of heritage culture may not accurately reflect international students' personal identification with their heritage culture. Therefore, further research is needed to illuminate the role of studying abroad in deconstructing general culture and contextualizing students' assumed fixed identity.